Laparoscopic Surgery for Endocrine Pancreatic Tumors: Experience of a Referral Center - Boniardi, Marco; Sartori, Paola V; Andreani, Sara; Pauna, Juliana; Ferrari, Giovanni C; Mutignani, Massimiliano; Pugliese, Raffaele (JOP. Journal of the Pancreas, 2012)
Context Laparoscopic pancreatic surgery is not common practice in Italy and is carried out in few centers. The reasons for this are manifold, such as the current selection of patients and both skills in laparoscopic and pancreatic surgery, are necessary to perform this operation safely. Objective We report the experience of a referral center for laparoscopic surgery comparing outcomes of laparoscopic and open procedures for endocrine pancreatic neoplasms. Materials Thirty patients (10 males and 20 females aged 57±14 years) were submitted to surgery for neuroendocrine pancreatic tumors from 2001 to 2010. Apart of 7 patients undergone duodenopancreatectomy, 13 patients received laparoscopic surgery and 10 open surgery. Results Mean overall operating time and postoperative hospital staying were 268±97 minutes and 26±28 days, respectively. Mortality was nil; overall morbidity was 56.5%. When comparing laparoscopy and open procedures operating time, postoperative hospital staying and even morbidity rate were similar (P>0.05). Conclusions Laparoscopic pancreatic surgery for endocrine tumors is safe and boasts a complication rate similar to that of open surgery. However, since it is a demanding procedure, it should be performed only in selected centers with a consolidated experience in laparoscopic and pancreatic surgery.